2022
DOI: 10.1038/s41598-022-05329-1
|View full text |Cite|
|
Sign up to set email alerts
|

Coastal flooding and mean sea-level rise allowances in atoll island

Abstract: Atoll islands are among the places most vulnerable to climate change due to their low elevation above mean sea level. Even today, some of these islands suffer from severe flooding generated by wind-waves, that will be exacerbated with mean sea-level rise. Wave-induced flooding is a complex physical process that requires computationally-expensive numerical models to be reliably estimated, thus limiting its application to single island case studies. Here we present a new model-based parameterisation for wave set… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 54 publications
0
12
0
Order By: Relevance
“…If we consider our projections, the exceedance of 2m of global mean sea‐level rise would be delayed by over 250 years by following the lower of the two scenarios (median estimate of 2249 for SSP2‐4.5, beyond 2500 for SSP1‐2.6), that is, keeping to the upper limit of the Paris Agreement, as can be seen in Figure 7. Although this may not prevent erosion or submergence of small atoll islands, this would grant more time for adaptation efforts such as relocation of communities or artificial island‐raising (Amores et al., 2022; Brown et al., 2023; van der Pol et al., 2023). Besides this mitigation challenge, adaptation requires a range of projections that depends on stakeholders' time horizons and risk aversions (Hinkel et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…If we consider our projections, the exceedance of 2m of global mean sea‐level rise would be delayed by over 250 years by following the lower of the two scenarios (median estimate of 2249 for SSP2‐4.5, beyond 2500 for SSP1‐2.6), that is, keeping to the upper limit of the Paris Agreement, as can be seen in Figure 7. Although this may not prevent erosion or submergence of small atoll islands, this would grant more time for adaptation efforts such as relocation of communities or artificial island‐raising (Amores et al., 2022; Brown et al., 2023; van der Pol et al., 2023). Besides this mitigation challenge, adaptation requires a range of projections that depends on stakeholders' time horizons and risk aversions (Hinkel et al., 2019).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a meta-analysis of published studies of multidecadal and shoreline changes across 30 atolls comprising 709 islands in the Indian and Pacific oceans found that despite annual changes in sea-level of between 2 and 3.9 mm only 11.4% had contracted, 15.5% increased in area, and 73.1% remained stable, with large islands more likely to be stable or increase in area [26]. Both sides of the debate tend to agree that there will be some degree of self-organization in response to morphodynamical feedbacks such that atoll islands may roll-back towards lagoons, with the question being how many are able to respond in this way, under which conditions, and for how long [27][28][29]. Some studies indicate larger atolls and wider and higher islands with wider reef flats will experience less erosion, suggesting these may be sites where future investments in critical infrastructure such as airports, hospitals and government centres could be concentrated [25,30,31].…”
Section: (A) Risks From Sea-level Risementioning
confidence: 99%
“…However, more recent studies using both field-based and modelling approaches indicate a broader suite of future outcomes for small islands and their communities, in which islands will continue to persist and remain available for habitation 1 , 6 , 10 . Modelling of wave interactions with reef systems and island shorelines indicates atoll islands will be subject to an increased frequency of flooding and likely salinization of groundwater tables 1 , 11 . For modelling purposes, these studies assumed that the geomorphic structure of islands, including size and elevation, remain constant, whereas remote sensing 12 17 and field-based studies 18 , 19 have highlighted the dynamic physical characteristics of islands which can change their shape, size, location and elevation on coral reef platforms from event to multi-decadal timescales.…”
Section: Introductionmentioning
confidence: 99%